The monophonic music in the roman de Fauvel - Harrison, Gregory Alexander Jr. (Michigan University microfilms international, 1982)
A dissertation submitted to the department of music and the committee on the graduate division of Stanford University in partial filfillment of the requirements for the degree of doctor of philosophy. 1963